Spectral analysis of stress symptoms caused by apple powdery mildew (Podosphaera leucotricha - Nagy, Attila; Riczu, Péter; Tamás, János (Acta Agraria Debreceniensis, 2014)
An orchard can be examined on the basis of spectral data, using methods with which the reflected radiation can be divided into a large number of (several hundreds) small spectral channel (some nm). Calculated on the basis of such hyperspectral data from different index numbers the water supply of foliage conditions can be well characterized. The research site is an intensive apple orchard, which located in University of Debrecen, Agricultural Sciences Centre, Farm and Regional Research Institute at Pallag. During my experiments the preliminary evaluation of spectral, non-invasive measurement method are carried out for detecting stress symptoms caused by Podosphaera leucotricha. Based on the results narrow band greenness indices (NDVI705, mNDVI705, mSR705 and REP) can be used for determination of diseased canopy and for the detection of stress symptoms of Podosphaera leucotricha,. These statements can be utilized in precision plant protection systems, since it can be a basis for such integrated active sensors with LED or laser light source, measuring reflectance at the certain spectral range, which can facilitate real time status assessment of orchards and can control precision fungicide utilization.